An autonomous self-healing mechanism to improve the chemical durability vs. moisture of PVDF-based gel electrolytes for lithium-ion batteries - Eleonora Carena; Caterina Colombo; Chiara Ferrara; Riccardo Ruffo; Piercarlo Mustarelli (Electrochemistry Communications, 2024)
Lithium-ion batteries (LIBs) are at the forefront of electrochemical energy storage both for consumer electronics, and for power/energy more demanding applications, such as in automotive and grid levelling. However, their chemical and electrochemical stability must be further improved. Among the instability causes, a major role is played by residual moisture. As a matter of fact, hydrofluoric acid generated by hydrolysis of LiPF6, the most common lithium salt in LIBs, causes safety issues and performance losses. Here we demonstrate the scavenging properties vs. HF of a barium silicate glass used as a filler in a PVDF-HFP based gel polymer electrolyte. A full LiTi2(PO4)3|electrolyte|LiMn2O4 cell is stable for 200 cycles at 0.1C.